Pelatihan Videografi untuk Mengembangkan Keterampilan Teknologi dalam Pendidikan Islam Di SMP Birrul Walidain Muhammadiyah Plupuh Sragen - Ria Khasna Mursyada; Nurkholimah Nanda Dewi Pertiwi; Nabilla Alya Nandicha; Abdul Rozaq; Muhamad Irfan Praditya; Guntur Cahyono (CV. ULIL ALBAB CORP, 2024)
The videography training at SMP Birrul Walidain Plupuh Sragen aims to enhance students' technological skills. In the face of rapid technological growth, integrating practical digital skills in education is crucial. The training covers basic videography concepts, hands-on practice, and the use of the CapCut app for editing. Implementation methods include planning, socialization, execution, and evaluation. Videography training involves 7th, 8th, and 9th-grade students, starting with basic video techniques, including recording and editing using the CapCut app on students' phones. This training not only expands students' knowledge of relevant subjects in the contemporary era but also strengthens cooperation skills, fosters positive social relationships, and nurtures their creativity. In the context of Islamic education, videography is considered a means to disseminate religious teachings and positive messages to society. It is hoped that this younger generation will become proficient technology users, support religious values, contribute positively to society, and continue learning.